The Five Elements of Professional Networking. - Lee, Christopher K.; ProQuest (firma) (La Vergne : Morgan James Publishing, 2025)
Networking.For many people, the word conjures up images of stuffy events--shaking hands, making small talk, and exchanging business cards.To them, "networking" feels forced, awkward, even disingenuous.It doesn't have to be this way.True networking is more than attending events and trading favors.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2025. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books